(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2023)
Diabetic ketoacidosis is the complicationof Diabetes mellitus, which can result due to extreme hyperglycemia and ketonaemia. This condition is prevalent among patients with untreated diabetes ordrug incompliance. Hyperglycemic hyperosmolar state can clinically be presented with episodes of seizures with high blood sugar levels and absence of ketones and has low incidence rate. A 55 year old male patient presented with episode of seizure, frothing, tongue bite, uprolling of eyes, shortness of breath, pedal edema and high blood sugar levels. Past medical history includes known hypertensive and diabetic since 10 years and is oninj regular insulin with non-adherence to medication. Lab investigations were performed and patient was diagnosed as hyperglycemic diabetic ketoacidosis secondary to drug incompliance. The patient was managed by insulin regimen- regular and basal insulin, antibiotics, antiepileptic drugs and by continuous monitoring of blood sugar levels every 3rd hourly. Diabetic ketoacidosis was recovered and later, there were no episodes of seizures. Creating awareness and proper patient education regarding the disease state, pharmacotherapy and drug compliance plays a vital role in managing the condition and as well as by preventing further complications that might be fatal in some cases.